Weather-resistant adhesive and preparation method thereof

CN119875550AInactive Publication Date: 2025-04-25DONGGUAN GUANGCHENG ADHESIVE PRODUCTS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411438057.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During use, epoxy resin adhesives are easily affected by the environment such as heat oxygen, ultraviolet rays, moisture, etc., resulting in poor weather resistance and reduced adhesion performance.

Method used

Weather-resistant adhesives with epoxy resin as the matrix are used to improve the adhesive properties and weather resistance by adding modified polyacrylic acid, nano zinc oxide and other additives. The modified polyacrylic acid introduces polar groups, triazine structure and hindered phenol structure to enhance adhesion and weather resistance; nano zinc oxide promotes curing and absorbs ultraviolet rays, and extends service life.

Benefits of technology

It significantly improves the adhesive properties and weather resistance, enhances its resistance to high temperatures, ultraviolet rays and moisture, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005085621100000101
    Figure BDA0005085621100000101
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and discloses a weather-resistant adhesive and a preparation method thereof. According to the adhesive prepared by the invention, the epoxy resin is taken as matrix resin, and the modified polyacrylic acid, the nano zinc oxide and other auxiliaries are added, so that the adhesive property and the weather resistance of the adhesive are improved; wherein a polar group, a triazine structure and a hindered phenol structure introduced into the modified polyacrylic acid have a synergistic effect, so that the adhesion and weather resistance of a matrix are improved, and nano zinc oxide is added, so that the curing process of the adhesive can be promoted, and meanwhile, the nano zinc oxide serving as an ultraviolet light absorber can absorb ultraviolet light and convert the ultraviolet light into harmless heat energy; damage of ultraviolet rays to the adhesive is reduced, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to a weather-resistant adhesive and a preparation method thereof. Background Art

[0002] Adhesives are a kind of adhesive that combines two surfaces together through chemical force, physical force or both to form a tough and stable adhesive layer, and have a certain strength after curing. Among them, adhesives based on epoxy resin have the advantages of easy curing, low shrinkage, low mechanical properties, good corrosion resistance, etc., and have a wide range of application prospects, such as: construction and decoration fields, automobile manufacturing and maintenance fields, shipbuilding and aviation fields, furniture manufacturing fields, electronic and electrical fields, etc.

[0003] However, epoxy resin adhesives also have some disadvantages. For example, during use, epoxy resin adhesives are easily affected by heat, oxygen, ultraviolet rays, moisture, etc. in the external environment, which leads to poor weather resistance of the adhesive, and then reduces the bonding performance of the adhesive. Therefore, it is necessary to modify the adhesive to address the problem of poor weather resistance, add various additives or resin materials with good weather resistance, and then improve the weather resistance of the adhesive and extend its service life. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a weather-resistant adhesive and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A weather-resistant adhesive comprises the following raw materials in parts by weight: 35-55 parts of epoxy resin, 10-20 parts of modified polyacrylic acid, 0.5-3 parts of leveling agent, 0.8-1.5 parts of accelerator, 3-8 parts of diluent, 12-17 parts of curing agent, and 2-4 parts of nano zinc oxide;

[0007] Furthermore, the epoxy resin is UVR 6110, the leveling agent is polyether silicone oil, the accelerator is 2-methylimidazole, the diluent is benzyl alcohol, and the curing agent is EH-451K;

[0008] The modified polyacrylic acid is prepared by the following steps:

[0009] Step A1, allylamine and sodium hydroxide are dispersed in acetone, which is referred to as solution 1; cyanuric chloride is dispersed in acetone, and solution 1 is slowly added dropwise, and the mixture is reacted at 0-5° C. for 3-4 hours to obtain intermediate product 1;

[0010] Step A2, dispersing 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and sodium hydroxide in acetone, recorded as solution 2; heating the intermediate product 1 to 45-55° C., adding half the volume of solution 2 to react for 6-8 hours, then heating to 90° C., adding the remaining solution 2, continuing to react for 8-10 hours, and filtering to obtain the intermediate product 2;

[0011] Step A3, add 3,4-dihydroxybenzoic acid and N,N-dimethylformamide to the intermediate product 2, mix and stir evenly, heat to 120-140°C under nitrogen, condense and reflux for 5-7h, after the reaction is completed, heat to 150°C again and continue to react for 2-3h, filter, wash and dry to obtain the functional monomer;

[0012] Step A4, mixing the emulsifier and deionized water evenly, then adding acrylic acid, methyl methacrylate, ethyl acrylate, functional monomer and maleic anhydride and stirring for 30-50 minutes to form a pre-emulsion; then dispersing ammonium persulfate in deionized water, heating to 60-80° C. and stirring for 30 minutes, adding the pre-emulsion dropwise within 1-2 hours, then heating to 80-90° C. and continuing the reaction for 2-4 hours, filtering, and obtaining polyacrylic acid;

[0013] Step A5, dispersing 4-dimethylaminopyridine in acetone, recorded as catalyst solution; dispersing polyacrylic acid and 2,5-di-tert-butylhydroquinone in acetone uniformly, then slowly adding the catalyst solution dropwise, and then adding triethylamine, 2-chloro-1-methylpyridinium iodide and dichloromethane in sequence, and stirring the reaction under nitrogen for 24 hours, rotary evaporation, and then adding 250 mL of acetone and stirring for 30 minutes, centrifuging, washing, and drying to obtain modified polyacrylic acid;

[0014] Further, in step A1, the usage ratio of cyanuric chloride, acetone and solution 1 is 0.1-0.3 mol: 200 mL: 100 mL, and the usage ratio of allylamine, sodium hydroxide and acetone in solution 1 is 0.1-0.3 mol: 4-8 g: 100 mL;

[0015] Further, in step A2, the ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, sodium hydroxide and acetone in solution 2 is 0.2-0.6 mol: 8-16 g: 200 mL;

[0016] Further, the molar ratio of 3,4-dihydroxybenzoic acid in step A3 to 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane in step A2 is 1:1, and the mass of N,N-dimethylformamide is 100 times the mass of the intermediate product 2 and 3,4-dihydroxybenzoic acid;

[0017] Further, in step A4, the mass ratio of ammonium persulfate, deionized water and pre-emulsion in the polyacrylic acid is 0.05-0.2:50-100:61-72-99;

[0018] Further, the mass ratio of the emulsifier, deionized water, acrylic acid, methyl methacrylate, ethyl acrylate, functional monomer and maleic anhydride in the pre-emulsion of step A4 is 1-3:40-60:4-7:8-12:5-9:2-5:1-3;

[0019] Further, in step A5, the usage ratio of polyacrylic acid, 2,5-di-tert-butylhydroquinone, acetone, catalyst solution, triethylamine, 2-chloro-1-methylpyridinium iodide and dichloromethane is 5-10 g: 0.02-0.06 mol: 50 mL: 30 mL: 0.02-0.03 mol: 0.005-0.01 mol: 10-20 mL;

[0020] Furthermore, the dosage ratio of 4-dimethylaminopyridine to acetone in the catalyst solution of step A5 is 0.003-0.009 mol:30 mL.

[0021] A method for preparing a weather-resistant adhesive comprises the following steps:

[0022] Step S1, weighing raw materials by weight, and evenly mixing epoxy resin, modified polyacrylic acid, nano zinc oxide, leveling agent, accelerator and diluent to obtain a mixture;

[0023] Step S2: adding a curing agent to the mixture and mixing evenly to obtain a weather-resistant adhesive.

[0024] Beneficial effects of the present invention:

[0025] The adhesive prepared by the present invention uses epoxy resin as a base resin, and adds modified polyacrylic acid, nano zinc oxide and other additives to improve the bonding performance and weather resistance of the adhesive; wherein the polar group, triazine structure and hindered phenol structure introduced into the modified polyacrylic acid synergistically improve the adhesion and weather resistance of the base, and the addition of nano zinc oxide can promote the curing process of the adhesive, and at the same time, as an ultraviolet absorber, it can absorb ultraviolet rays and convert them into harmless heat energy, thereby reducing the damage of ultraviolet rays to the adhesive and extending the service life.

[0026] In the modified polyacrylic acid, the -Cl in cyanuric chloride and the -NH in allylamine are first used to 2The method comprises the steps of: reacting the intermediate product 1 with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to generate an intermediate product 2; reacting the intermediate product 2 with 3,4-dihydroxybenzoic acid to generate a functional monomer containing a triazine structure and a catechol structure; using acrylic acid, methyl methacrylate, ethyl acrylate, the functional monomer and maleic anhydride as raw materials to synthesize a polyacrylic acid containing a maleic anhydride structure; and finally utilizing the ring-opening reaction of maleic anhydride in the polyacrylic acid and 2,5-di-tert-butylhydroquinone to generate a modified polyacrylic acid containing a hindered phenol structure.

[0027] The introduction of modified polyacrylic acid improves the adhesion and weather resistance of the adhesive. This is because the polyacrylic acid resin molecule contains a double bond structure, has good fluidity and deformability, can fully penetrate and fill the tiny depressions on the surface of the object to form a dense bonding layer, and at the same time, the polar groups in its molecules can interact with the polar groups on the surface of the bonded material to form intermolecular adsorption forces, further enhancing the bonding properties of the matrix; during the curing process of the adhesive, the polyacrylic acid resin can also form a three-dimensional cross-linked network structure through a cross-linking reaction, thereby improving the water resistance of the matrix and thereby enhancing the weather resistance of the matrix.

[0028] The modified polyacrylic acid contains triazine structure and hindered phenol structure, which can prevent or inhibit chain initiation reaction and chain growth reaction by capturing peroxy radicals, thereby terminating the free radical chain reaction and delaying the aging of the matrix caused by the external environment, thereby improving the weather resistance of the matrix and increasing the service life, while avoiding the decline in weather resistance caused by migration and precipitation. In addition, the catechol structure with strong adhesion is introduced into the matrix, which can not only improve the bonding performance of the matrix, but also improve the heat resistance of the adhesive, so that it can still maintain a good bonding effect under high temperature environment. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] Modified polyacrylic acid is prepared by the following steps:

[0032] Step A1, 0.1 mol of allylamine and 4 g of sodium hydroxide were dispersed in 100 mL of acetone, recorded as solution 1; 0.1 mol of cyanuric chloride was dispersed in 200 mL of acetone, and then 100 mL of solution 1 was slowly added dropwise, and the mixture was reacted at 0° C. for 3 h to obtain intermediate product 1;

[0033] Step A2, 0.2 mol 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 8 g sodium hydroxide were dispersed in 200 mL acetone, recorded as solution 2; the intermediate product 1 was heated to 45° C., 100 mL of solution 2 was added and reacted for 6 h, then the temperature was raised to 90° C., the remaining 100 mL of solution 2 was added, the reaction was continued for 8 h, and suction was filtered to obtain the intermediate product 2;

[0034] Step A3, adding 3,4-dihydroxybenzoic acid and N,N-dimethylformamide to the intermediate product 2, mixing and stirring evenly, heating to 120°C under nitrogen conditions, condensing and reflux for 5 hours, and after the reaction is completed, heating to 150°C again to continue the reaction for 2 hours, filtering, washing, and drying to obtain a functional monomer, wherein the molar ratio of 3,4-dihydroxybenzoic acid to 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane in step A2 is 1:1, and the mass of N,N-dimethylformamide is 100 times the mass of the intermediate product 2 and 3,4-dihydroxybenzoic acid;

[0035] Step A4, 1g of emulsifier and 40g of deionized water were mixed evenly, and then 4g of acrylic acid, 8g of methyl methacrylate, 5g of ethyl acrylate, 2g of functional monomer and 1g of maleic anhydride were added and stirred for 30min to form a pre-emulsion; then 0.05g of ammonium persulfate was dispersed in 50g of deionized water, heated to 60°C and stirred for 30min, 61g of the pre-emulsion was added dropwise within 1h, and then the temperature was raised to 80°C and the reaction was continued for 2h, and filtered to obtain polyacrylic acid;

[0036] Step A5, 0.003 mol 4-dimethylaminopyridine was dispersed in 30 mL acetone, recorded as the catalyst solution; 5 g polyacrylic acid and 0.02 mol 2,5-di-tert-butylhydroquinone were evenly dispersed in 50 mL acetone, and then 30 mL of the catalyst solution was slowly added dropwise, and then 0.02 mol triethylamine, 0.005 mol 2-chloro-1-methylpyridinium iodide and 10 mL dichloromethane were added in sequence, and stirred for 24 h under nitrogen conditions, rotary evaporated, and then 250 mL acetone was added and stirred for 30 min, centrifuged, washed, and dried to obtain modified polyacrylic acid.

[0037] Example 2

[0038] Modified polyacrylic acid is prepared by the following steps:

[0039] Step A1, 0.2 mol of allylamine and 6 g of sodium hydroxide were dispersed in 100 mL of acetone, recorded as solution 1; 0.2 mol of cyanuric chloride was dispersed in 200 mL of acetone, and then 100 mL of solution 1 was slowly added dropwise, and reacted at 2° C. for 3.5 hours to obtain intermediate product 1;

[0040] Step A2, 0.4 mol 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 12 g sodium hydroxide were dispersed in 200 mL acetone, recorded as solution 2; the intermediate product 1 was heated to 50° C., 100 mL of solution 2 was added and reacted for 7 h, then the temperature was raised to 90° C., the remaining 100 mL of solution 2 was added, the reaction was continued for 9 h, and suction was filtered to obtain the intermediate product 2;

[0041] Step A3, add 3,4-dihydroxybenzoic acid and N,N-dimethylformamide to the intermediate product 2, mix and stir evenly, heat to 130°C under nitrogen, condense and reflux for 6 hours, and after the reaction is completed, heat to 150°C again to continue the reaction for 2.5 hours, filter, wash and dry to obtain a functional monomer, the molar ratio of 3,4-dihydroxybenzoic acid and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane in step A2 is 1:1, and the mass of N,N-dimethylformamide is 100 times the mass of the intermediate product 2 and 3,4-dihydroxybenzoic acid;

[0042] Step A4, 2g of emulsifier and 50g of deionized water were mixed evenly, and then 5g of acrylic acid, 10g of methyl methacrylate, 7g of ethyl acrylate, 3g of functional monomer and 2g of maleic anhydride were added and stirred for 40min to form a pre-emulsion; then 0.1g of ammonium persulfate was dispersed in 75g of deionized water, heated to 70°C and stirred for 30min, and 79g of the pre-emulsion was added dropwise within 1.5h, and then the temperature was raised to 85°C and the reaction was continued for 3h, and filtered to obtain polyacrylic acid;

[0043] Step A5, 0.006 mol 4-dimethylaminopyridine was dispersed in 30 mL acetone, recorded as the catalyst solution; 7 g polyacrylic acid and 0.04 mol 2,5-di-tert-butylhydroquinone were evenly dispersed in 50 mL acetone, and then 30 mL of the catalyst solution was slowly added dropwise, and then 0.025 mol triethylamine, 0.0075 mol 2-chloro-1-methylpyridinium iodide and 15 mL dichloromethane were added in sequence, and stirred for reaction under nitrogen for 24 h, rotary evaporated, and then 250 mL acetone was added and stirred for 30 min, centrifuged, washed, and dried to obtain modified polyacrylic acid.

[0044] Example 3

[0045] Modified polyacrylic acid is prepared by the following steps:

[0046] Step A1, 0.3 mol of allylamine and 8 g of sodium hydroxide were dispersed in 100 mL of acetone, recorded as solution 1; 0.3 mol of cyanuric chloride was dispersed in 200 mL of acetone, and then 100 mL of solution 1 was slowly added dropwise, and the mixture was reacted at 5° C. for 4 h to obtain intermediate product 1;

[0047] Step A2, 0.6 mol 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 16 g sodium hydroxide were dispersed in 200 mL acetone, recorded as solution 2; the intermediate product 1 was heated to 55° C., 100 mL of solution 2 was added and reacted for 8 h, then the temperature was raised to 90° C., the remaining 100 mL of solution 2 was added, the reaction was continued for 10 h, and suction was filtered to obtain the intermediate product 2;

[0048] Step A3, add 3,4-dihydroxybenzoic acid and N,N-dimethylformamide to the intermediate product 2, mix and stir evenly, heat to 140°C under nitrogen, condense and reflux for 7h, after the reaction is completed, heat to 150°C again and continue to react for 3h, filter, wash and dry to obtain a functional monomer, the molar ratio of 3,4-dihydroxybenzoic acid and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane in step A2 is 1:1, and the mass of N,N-dimethylformamide is 100 times the mass of the intermediate product 2 and 3,4-dihydroxybenzoic acid;

[0049] Step A4, 3g of emulsifier and 60g of deionized water were mixed evenly, and then 7g of acrylic acid, 12g of methyl methacrylate, 9g of ethyl acrylate, 5g of functional monomer and 3g of maleic anhydride were added and stirred for 50min to form a pre-emulsion; then 0.2g of ammonium persulfate was dispersed in 100g of deionized water, heated to 80°C and stirred for 30min, and 99g of the pre-emulsion was added dropwise within 2h, and then the temperature was raised to 90°C and the reaction was continued for 4h, and filtered to obtain polyacrylic acid;

[0050] Step A5, 0.009 mol 4-dimethylaminopyridine was dispersed in 30 mL acetone, recorded as the catalyst solution; 10 g polyacrylic acid and 0.06 mol 2,5-di-tert-butylhydroquinone were evenly dispersed in 50 mL acetone, and then 30 mL of the catalyst solution was slowly added dropwise, and then 0.03 mol triethylamine, 0.01 mol 2-chloro-1-methylpyridinium iodide and 20 mL of dichloromethane were added in sequence, and stirred for reaction under nitrogen for 24 h, rotary evaporated, and then 250 mL acetone was added and stirred for 30 min, centrifuged, washed, and dried to obtain modified polyacrylic acid.

[0051] Example 4

[0052] A method for preparing a weather-resistant adhesive comprises the following steps:

[0053] 35 parts of epoxy resin (UVR 6110), 10 parts of modified polyacrylic acid prepared in Example 1, 0.5 parts of leveling agent (polyether silicone oil), 0.8 parts of accelerator (2-methylimidazole), 3 parts of diluent (benzyl alcohol), 12 parts of curing agent (EH-451K), and 2 parts of nano zinc oxide;

[0054] Step S1, weighing raw materials by weight, and evenly mixing epoxy resin, modified polyacrylic acid prepared in Example 1, nano zinc oxide, leveling agent, accelerator and diluent to obtain a mixture;

[0055] Step S2: adding a curing agent to the mixture and mixing evenly to obtain a weather-resistant adhesive.

[0056] Example 5

[0057] A method for preparing a weather-resistant adhesive comprises the following steps:

[0058] 45 parts of epoxy resin (UVR 6110), 15 parts of modified polyacrylic acid prepared in Example 2, 1 part of leveling agent (polyether silicone oil), 1.2 parts of accelerator (2-methylimidazole), 5 parts of diluent (benzyl alcohol), 15 parts of curing agent (EH-451K), 3 parts of nano zinc oxide;

[0059] Step S1, weighing raw materials by weight, and evenly mixing epoxy resin, modified polyacrylic acid prepared in Example 2, nano zinc oxide, leveling agent, accelerator and diluent to obtain a mixture;

[0060] Step S2: adding a curing agent to the mixture and mixing evenly to obtain a weather-resistant adhesive.

[0061] Example 6

[0062] A method for preparing a weather-resistant adhesive comprises the following steps:

[0063] 55 parts of epoxy resin (UVR 6110), 20 parts of modified polyacrylic acid prepared in Example 3, 3 parts of leveling agent (polyether silicone oil), 1.5 parts of accelerator (2-methylimidazole), 8 parts of diluent (benzyl alcohol), 17 parts of curing agent (EH-451K), 4 parts of nano zinc oxide;

[0064] Step S1, weighing raw materials by weight, and evenly mixing epoxy resin, modified polyacrylic acid prepared in Example 3, nano zinc oxide, leveling agent, accelerator and diluent to obtain a mixture;

[0065] Step S2: adding a curing agent to the mixture and mixing evenly to obtain a weather-resistant adhesive.

[0066] Comparative Example 1

[0067] This comparative example is an adhesive, which is different from Example 6 in that commercially available polyacrylic acid is used instead of the modified polyacrylic acid prepared in Example 3, and the rest is the same.

[0068] Comparative Example 2

[0069] This comparative example is an adhesive, which differs from Example 6 in that commercially available polyacrylic acid is used instead of the modified polyacrylic acid prepared in Example 3, and 3 parts of antioxidant 1010 are added to the mixture, and the rest are the same.

[0070] The adhesives prepared in Examples 4-6 and Comparative Examples 1-2 were used as bonding substrates on aluminum alloy plates with specifications of 200×25×2 mm, and a film with a thickness of 0.2 mm was scraped and dried with hot air at 50°C for 1 hour, and then naturally cured for 24 hours to obtain samples. The peel strength test was performed according to GB / T 7122-1996, the tensile strength test was performed according to GB / T 1040.1-2018, and the artificial accelerated aging was performed according to GB / T 14522-2008. The parameters of one cycle were set as follows: UVB-313 ultraviolet irradiation + temperature of 60°C, treatment for 4 hours, ultraviolet irradiation + spray water, treatment for 4 hours, and the total cycle time was 168 hours. The treated film was taken for further tensile strength test;

[0071] The test results are shown in the following table:

[0072]

[0073] It can be seen from the above table that after performance testing, the peel strength of the adhesive prepared by the present invention is in the range of 5.34 kN / m-5.87 kN / m, the initial tensile strength is in the range of 62.3 MPa-66.1 MPa, and the tensile strength after artificial aging is in the range of 38.4 MPa-42.5 MPa, indicating that the adhesive has excellent bonding performance and weather resistance.

[0074] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A weather-resistant adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 35-55 parts of epoxy resin, 10-20 parts of modified polyacrylic acid, 0.5-3 parts of leveling agent, 0.8-1.5 parts of accelerator, 3-8 parts of diluent, 12-17 parts of curing agent and 2-4 parts of nano zinc oxide; The modified polyacrylic acid is prepared by the following steps: Step A1, allylamine and sodium hydroxide are dispersed in acetone, which is referred to as solution 1; cyanuric chloride is dispersed in acetone, and solution 1 is slowly added dropwise, and the mixture is reacted at 0-5° C. for 3-4 hours to obtain intermediate product 1; Step A2, dispersing 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and sodium hydroxide in acetone, recorded as solution 2; heating the intermediate product 1 to 45-55° C., adding half the volume of solution 2 to react for 6-8 hours, then heating to 90° C., adding the remaining solution 2, continuing to react for 8-10 hours, and filtering to obtain the intermediate product 2; Step A3, add 3,4-dihydroxybenzoic acid and N,N-dimethylformamide to the intermediate product 2, mix and stir evenly, heat to 120-140°C under nitrogen, condense and reflux for 5-7h, after the reaction is completed, heat to 150°C again and continue to react for 2-3h, filter, wash and dry to obtain the functional monomer; Step A4, mixing the emulsifier and deionized water evenly, then adding acrylic acid, methyl methacrylate, ethyl acrylate, functional monomer and maleic anhydride and stirring for 30-50 minutes to form a pre-emulsion; then dispersing ammonium persulfate in deionized water, heating to 60-80° C. and stirring for 30 minutes, adding the pre-emulsion dropwise within 1-2 hours, then heating to 80-90° C. and continuing the reaction for 2-4 hours, filtering, and obtaining polyacrylic acid; Step A5, dispersing 4-dimethylaminopyridine in acetone, recorded as catalyst solution; dispersing polyacrylic acid and 2,5-di-tert-butylhydroquinone in acetone evenly, then slowly adding the catalyst solution dropwise, and then adding triethylamine, 2-chloro-1-methylpyridinium iodide and dichloromethane in sequence, and stirring the reaction under nitrogen for 24 hours, rotary evaporation, and then adding 250 mL of acetone and stirring for 30 minutes, centrifuging, washing, and drying to obtain modified polyacrylic acid.

2. A weather-resistant adhesive according to claim 1, characterized in that: In step A1, the usage ratio of cyanuric chloride, acetone and solution 1 is 0.1-0.3 mol: 200 mL: 100 mL, and the usage ratio of allylamine, sodium hydroxide and acetone in solution 1 is 0.1-0.3 mol: 4-8 g: 100 mL.

3. A weather-resistant adhesive according to claim 1, characterized in that: In step A2, the amount ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, sodium hydroxide and acetone in solution 2 is 0.2-0.6 mol: 8-16 g: 200 mL.

4. The weather-resistant adhesive according to claim 1, characterized in that: The molar ratio of 3,4-dihydroxybenzoic acid in step A3 and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane in step A2 is 1:1, and the mass of N,N-dimethylformamide is 100 times the sum of the mass of the intermediate product 2 and 3,4-dihydroxybenzoic acid.

5. The weather-resistant adhesive according to claim 1, characterized in that: In step A4, the mass ratio of ammonium persulfate, deionized water and pre-emulsion in the polyacrylic acid is 0.05-0.2:50-100:61-72-99.

6. The weather-resistant adhesive according to claim 1, characterized in that: The mass ratio of the emulsifier, deionized water, acrylic acid, methyl methacrylate, ethyl acrylate, functional monomer and maleic anhydride in the pre-emulsion of step A4 is 1-3:40-60:4-7:8-12:5-9:2-5:1-3.

7. The weather-resistant adhesive according to claim 1, characterized in that: In step A5, the usage ratio of polyacrylic acid, 2,5-di-tert-butylhydroquinone, acetone, catalyst solution, triethylamine, 2-chloro-1-methylpyridinium iodide and dichloromethane is 5-10 g: 0.02-0.06 mol: 50 mL: 30 mL: 0.02-0.03 mol: 0.005-0.01 mol: 10-20 mL.

8. The weather-resistant adhesive according to claim 1, characterized in that: The amount ratio of 4-dimethylaminopyridine to acetone in the catalyst solution of step A5 is 0.003-0.009 mol:30 mL.

9. The weather-resistant adhesive according to claim 1, characterized in that: Furthermore, the leveling agent is polyether silicone oil, the accelerator is 2-methylimidazole, the diluent is benzyl alcohol, and the curing agent is EH-451K.

10. A method for preparing the weather-resistant adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight, and evenly mixing epoxy resin, modified polyacrylic acid, nano zinc oxide, leveling agent, accelerator and diluent to obtain a mixture; Step S2: adding a curing agent to the mixture and mixing evenly to obtain a weather-resistant adhesive.

Citation Information

Cited By

  • Organic polymer enhanced casting polypropylene medicine packaging film and preparation method thereof

    CN120923848A